Decolonial approach and critical discourse analysis: Theoretical convergences for organizational studies - Samanta Borges Pereira, Andreina del Carmen Camero de Lima, Mônica Carvalho Alves Cappelle (Opción, 2019)
The convergence between decolonial approach and Critical Discourse Analysis may represent a prolific path for organizational studies. This paper objective is to discuss and reflect about potential theoretical convergences between decolonial approach and CDA and their contributions to organizational studies. Relevant convergences between the approaches were identified, such as focus on social problems, concern with power relations, discussion about ideology and hegemony, the pursuit of movements of change and rupture with the social structures of domination, etc. It demonstrates the potential for organizational studies and confirms the possibility of using CDA as methodological support for applied decolonial research.